Characterization of industrial activated carbons by adsorption and immersion techniques and by STM - Stoeckli, Fritz; Centeno, Teresa A.; Donnet, Jean-Baptiste; Pusset, Nadia; Papirer, Eugéne (My University, 1995)
The results obtained from a variety of techniques (vapour adsorption, selective adsorption of caffeine and immersion calorimetry) used to characterize activated carbons of industrial origin are compared. It is shown that gate effects due to constrictions, and often overlooked, can be revealed by simple experiments with larger molecular probles. Immersion calorimetry appears to be a simple and efficient technique, as illustrated by an activation series. Complementary information is also provided by scanning tunnelling microscopy (STM).
Keywords: activated carbons; characterization; STM